Alleviation of Detrimental Effects of Salt Stress on Date Palm (Phoenix dactylifera L.) by the Application of Arbuscular Mycorrhizal Fungi and/or Compost - Mohamed Ait-El-Mokhtar; Marouane Baslam; Raja Ben-Laouane; Mohamed Anli; Abderrahim Boutasknit; Toshiaki Mitsui; Toshiaki Mitsui; Said Wahbi; Abdelilah Meddich (Frontiers in Sustainable Food Systems, 2020)
The date palm is a commercially important woody crop and is a good target plant for improving agricultural yields in extreme environments. However, salinity has been the primary abiotic stress complicating its cultivation and damaging its production worldwide. This study investigated the effect of alleviating salt stress on date palm growth and development by using arbuscular mycorrhizal fungi (AMF) and/or compost. The experiment was arranged in a completely randomized design with eight treatments. The treatments comprised control without inoculation or amendment and application of compost (made from green waste) and AMF (an autochthonous consortium) individually or in combination under non-saline (0 mM NaCl) or saline (240 mM NaCl) conditions. Growth, physiological characteristics, nutrient uptake, chlorophyll content, oxidative stress markers, and antioxidant enzyme activities were assessed. Salt stress increased sodium (Na+) and chlorine (Cl−) content, lipid peroxidation and proline, soluble sugar, and H2O2 content. However, it reduced growth parameters, AMF colonization, leaf water potential, nitrogen (N), phosphorus (P), potassium (K+), calcium (Ca2+), and chlorophyll content. The application of AMF and compost separately or in combination mitigated the deleterious effects induced by salinity. AMF inoculation contributed to plant salt tolerance through strategies such as increased nutrient uptake (particularly P and Ca2+), chlorophyll content, relative water content, stomatal conductance, antioxidant enzymatic activities (superoxide dismutase, ascorbate peroxidase, catalase) and by decreasing lipid peroxidation and H2O2 content. Plants grown in soil amended with compost under salt stress showed an improvement particularly in K+ and proline content and a decrease in H2O2 concentration compared to controls under the saline condition. In the presence of NaCl stress, the dual application of the compost and AMF consortium maximized plant growth, stomatal conductance, leaf water potential, all antioxidant enzyme activities and P, K+, N, and Ca2+ uptake as well as proline and soluble sugar content. However, it reduced Na+ and Cl− uptake and oxidative stress marker content. In conclusion, our study suggests that the application of AMF with compost has the potential to improve the tolerance of date palm seedlings to salt stress more than AMF or compost applied separately.